Upaya Pemberdayaan Santri Yayasan Pondok Pesantren Al-Majmuk Nw Jurang Jaler Melalui Mini Market Al-Majmuk Nw Jurang Jaler, Lombok Tengah - Saparwadi, Saparwadi; Hanisari, Nurmaema (International Conference on Islamic Studies, 2022)
The focus of this research is the effort to empower students of the al-majmuk Islamic boarding school foundation nw ravine through the mini market al-majmuk nw jaler jaler lombok being established as a media and minimarket that facilitates social problems experienced by students of the al-majmuk nw ravine Islamic boarding school foundation . The purpose of this study was to describe the efforts to empower students at the Al-Majmuk Islamic Boarding School in West Lombok through the Al-Majmuk mini market, Central Lombok. This study uses a qualitative descriptive research method, namely observing an object and interpreting it in the description of words. Collecting data in the study using observation, interviews and documentation. Data analysis in this study uses the Miles and Huberman model, namely by collecting data, presenting data in narrative text, and drawing conclusions. Informant retrieval in this study using a snowball. The results of this study indicate that from the empowerment carried out by the Al-Majmuk Islamic Boarding School, NW Jurang Jaler, there are three economic empowerment of Islamic boarding schools. First, entrepreneurship training for santri that they have potential that can be developed. second, providing capital to students by providing facilities and infrastructure for entrepreneurial activities. Third, mentoring the participation of students by implementing regulations that require students to participate in entrepreneurial activities.